PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN RASA PERCAYA DIRI SISWA KELAS X SMA NEGERI 2 MUARA BELITI - Basarudin, Basarudin (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
This study aims to evaluate the improvement of mathematical communication skills and student confidence through the application of the Problem Based Learning (PBL) model. The research subjects were grade X students at SMA Negeri 2 Muara Beliti in the 2024/2025 school year. This research used a quasi-experimental method with pretest-posttest control group design. The results showed that the application of the PBL model can significantly improve students' mathematical communication skills and self-confidence compared to conventional learning